Plan de comercialización de productos derribados de yuca en el Cantón La Maná, Provincia de Cotopaxi - Carreño Balseca, Stalin Gabriel (2017)
The main objective of this research project was to carry out a marketing plan for cassava products in La Maná town. The proposal was conceived as an alternative for the economic development of the micro-enterprise sector, which aim was to place itself in the market as an excellent marketer of empanadas of cassava in La Maná town. For the market study, surveys were conducted for the population of La Maná, using questionnaires with multiple choice questions as an instrument. This made possible to obtain data and relevant information on the demand for product preferences. The proposal of the feasibility study began with the determination of demand and supply, resulting in an unsatisfied demand of 1248,720 cassava empanadas, value that evidenced the existence of the market for the creation of microenterprise. The technical study showed in detail the size of the project, the processing and marketing process, the requirements of machinery, inputs and labor. Through the economic study it was established that the total investment was 71.087,98 of which 29.66% was obtained by contribution of the partners and 70.34% was financed by a bank loan to a term of 5 years to through monthly payments with an annual interest rate of 15%. The financial study revealed that the proposal had a net profit of 22.719,69 for the first period, a VAN of 34.686,84 and a TIR of 32,24%, which demonstrated the feasibility and profitability of the present proposal.